Preliminary evaluation of the hygienic level of refrigerated vacuum-packed wild boar meat - Caterina Altissimi; Mathieu Venuto; Marta Coppini; Raffaella Branciari; Rossana Roila; Sonia Esposto; David Ranucci (Italian Journal of Food Safety)
Wild boar meat is usually available frozen, but the catering industry is also interested in fresh vacuum-chilled meat. This work aims to evaluate the hygienic level of vacuum-packed and refrigerated game meat [Longissimus dorsi (LD) muscle] and to investigate the existence of relationships with other parameters measured at the game handling establishment (GHE). The pH of the LD muscle and carcass surface contamination [aerobic colony count (ACC) and Enterobacteriaceae (EC)] were measured on 12 wild boar regularly processed at a local GHE. Subsequently, 2 cm-thick steaks were taken from the LD muscle at a cutting plant from the same subjects sampled at the GHE and individually vacuum sealed and stored at 2°C for 1, 7, 14, and 21 days. The meat was analyzed for ACC and EC at each storage time and for Escherichia coli β-glucosidase + counts at 21 days. The mean final pH value of the muscle samples was 5.6, and the ACC and EC carcass surface average load was 2.54 and 0.79 Log CFU/cm2, respectively. Meat preparations at 21 days had ACC, EC, and E. coli mean values of 5.80, 3.13, and 2.03 Log CFU/g, respectively. Pearson’s analysis showed a significant positive correlation between pH and ACC at day 1 and between EC on carcasses and meat at day 1. The results confirm that if the pH of meat is high, the development of microorganisms is favored, and, therefore, a shorter shelf life is expected. Furthermore, the EC on carcasses seems to be a good index for estimating the hygienic level of the obtained meat.